A Conservative Bioadhesive Approach to the Reattachment of Complicated Crown Fractures in Permanent First Molars: A Case Report with a 2-Year Followup - Pragati Mirikar (Case Reports in Medicine)
This paper presents a clinical report demonstrating combined restorative bioadhesive treatment and prosthetic rehabilitation of uncommon type of dental injury in an eighteen-year-old female involving crown fracture of all the permanent first molars and left upper premolars due to a bicycle riding accident. To restore the coronal fracture with invasion of biologic width, flap surgery with osteotomy and osteoplasty localized on the fractured teeth was performed, and the tooth remnant was reattached to the crown with a self-etch adhesive system. Frank pulp exposure was treated by self-etch dentin adhesive after surface disinfection prior to sealing of the wound site. At 2-year recall, the teeth continue to be aesthetically and functionally stable with a favourable pulpal and periapical environment.